Evaluation of Lipid Profile and Liver Function After Administration of Scenedesmus dimorphus in Obese Mice - Armaini Armaini; Siti Hajir; Yetria Rilda (Universitas Andalas, 2022)
Obesity is a major public health problem in developing countries and is a significant risk factor for metabolic disorders. Microalgae Scenedesmus dimorphus (S. dimorphus) contains bioactive compounds such as pigment function as antioxidants, and omega-3 and omega-6 PUFAs have potential as nutraceuticals. The study aimed to evaluate the lipid profile and liver function after the administration of S. dimorphus in obese mice. The research design uses mice which are divided into 6 groups; Group 1 (G1) normal control, G2 control Obesity, G3 treatment with Orlistat, G4 treatment S. dimorphus (0.25mg/g BW), G5 treatment S. dimorphus (0.5 mg/g BW) and G6 treatment S. dimorphus (0.75 mg/g BW) each group consisted of 5 mice and 21 days of observation time. The parameters observed were lipid profile and liver function of mice. Based on the results of the study, the effective dose for treating obesity is a dose of S. dimorphus 0.75 mg/g (BW) can reduce cholesterol, triglycerides, and LDL levels, respectively 67.7 mg/dl, 49.2 mg/dl, 10 , 2 mg/dl, and increased HDL, 68.32 mg/dl compared to control of obesity (G2), respectively 108.7 mg/dl, 139.1 mg/dl, 20.6 mg/dl and HDL 60, 28 mg/dl, this dose is also effective for improving the function of blood pressure by reducing AST and ALT 15.6 U/L and 18.8 U/L, respectively, compared to the obesity group (G2), which is 26.6 U/L, and 29,7 U/L. Based on the results of the study it can be concluded that S. dimorphus is useful for anti-obesity for mice (Mus musculus).